Towards an Antarctic scenarios dashboard. Issue 2 (2nd July 2020) - Frame, Bob
ABSTRACT: This research note provides guidance for the development of simple indicators set in a dashboard format to illustrate current and future states of Antarctica. It supports increasing interest in the complexities of long-term futures relating to Antarctica. Scenario processes enable structured possibilities about the impacts and implications of multiple drivers of change that need to be integrated to enable effective decision making within the Antarctic Treaty System. Draft indicators for the Antarctic Scenarios Integrated Framework are presented in line with an organising structure analogous to the current practice of the Intergovernmental Panel on Climate Change. It draws on a concise set of elements that build on existing research, including social, economic and environmental factors. Current baseline data are available as described through a range of open-source online databases and information sources. The aim is to provide accessible heuristics for a complex and emerging phenomenon that may only be described through crude estimates of quantitative data or through qualitative impressions of geopolitical information over a time line of anywhere from five to a hundred years. In this sense, the indicators are concerned less with accuracy and more with their materiality in highly complex, uncertain circumstances and strong inter-relationships. The note ends with suggestions on how the dashboard could be further developed.